Analisis Beban Kerja pada Karyawan Gudang Logistik Farmasi di RS PKU Muhammadiyah Kota Yogyakarta dengan Menggunakan Metode Full Time Equivalent - Hibatullah, Fadhila Azzani; Syam, Nur Syarianingsih (International Journal of Healthcare Research, 2022)
Background: PKU Muhammadiyah Hospital of Yogyakarta City has a pharmacy logistics warehouse section / unit that has the task of receiving, storing, distributing, and managing supplies such as drugs, medical devices and other pharmaceutical supplies. The number of employees in the logistic pharmacy warehouse unit is 5 people. There are still some problems owned by employees of pharmaceutical logistics warehouses such as excess working time of about 8 hours in 1 month, double jobs in pharmaceutical engineering personnel in pharmacy warehouses. The purpose of this study is to analyze the workload owned by employees of the pharmacy logistics warehouse of PKU Muhammadiyah City Hospital yogyakarta using the Full Time Equivalent (FTE) method. Method: This research uses a type of qualitative research with a case study approach. The subjects of the interview and observation in this study were employees in a pharmacy logistic warehouse of 5 people. Data collection instruments use observation forms and interview guides, as well as in calculating workloads using the FTE method. Results: Working time is available owned by employees of pharmaceutical logistics warehouses as much as 7 hours per day or 1,918 hours per year. The leeway time on logistic warehouse employees is 30 minutes. All employees except storage and distribution II implementers have an FTE index below 1.00 which is having less workload or underload, while 1 employee implementing storage and distribution II has an FTE index in the range of 1.00-1.28 which means it has a normal workload. Conclusion: Based on FTE calculations, there are 4 employees who have an underload workload with a range of <1.00 and 1 employee has a normal workload by having an FTE index of 1.01.